PENGEMBANGAN E-MODUL BERBASIS DISCOVERY LEARNING MENGGUNAKAN APLIKASI CANVA PADA PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Wiwik Okta Susilawati; Riyadi Saputra; Sonia Yulia Friska; Erma Prabalingga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the lack of independent curriculum teaching materials that suit school needs. SDN 5 Sitiung requires teaching materials, one of which is the IPAS e-module in Class IV. So the effort made is to develop a Class IV science e-module for elementary schools in an independent curriculum that is valid, practical and effective. This type of research is Research and Development research which uses the Plomp development model which has several stages, namely (Preliminary research, development prototyping phase, assessment phase). The assessment instrument was carried out by the validators, namely content validator, language validator and graphic validator. Filling out the instrument sheet uses a validation sheet for validators and a practicality sheet assessed by practitioners. The result obtained from the development of Discovery Learning-Based E-Modules using the Canva Application in Class IV Science and Science Learning at Elementary School at SDN 5 Sitiung, namely from the validator results obtained an average of 89,3% with a very valid category, the practicality value obtained an average value of 94,2% in the very practical category, and the effectiveness value obtained an average of 83% in the very effective category.